Clostridium septicum Aortitis of the Infrarenal Abdominal Aorta - Shah, Aditya (J Clin Med Res, 2016)
Clostridium septicum aortitis is a rare infection that has a strong association with occult colonic malignancy. There is also emerging evidence to support the combination of medical and surgical management over medical management alone. To the best of our knowledge, we report the 40th known case of C. septicum aortitis.